Pengaruh Celebrity Endorse dan Electronic Word of Mouth terhadap Keputusan Pembelian pada Sosial Media Instagram : Survey pada Followers @tasyafarasya - Fonny Thasia Arsetya; Musthofa Hadi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The development of information technology marks the beginning of digitalization in marketing. In response to this, a company must determine their strategy to increase purchase decision. One of the strategies a company must do to increase public awareness is by applying online marketing. This research mainly focuses on @tasyafarasya’s Instagram account and is aimed to analyze the influence of celebrity endorsement and electronic word of mouth on purchase decision on Instagram. This research was a quantitative descriptive with 3 variables: celebrity endorsement, electronic word of mouth and purchase decision. The techniques used in collecting the data were observation and questionnaire using purposive sampling to get 100 respondents. Data was analyzed using linear regression analysis, determination coefficient and hypothesis test. The results of linear regression analysis showed that Y = 3.490+0.179X1+ 0.572X2+e. The determination coefficient was 0.494=49.4%. The t-calculation of celebrity endorsement showed 2.169>1.985 which means that there was a significant effect of celebrity endorsement on purchase decision, Meanwhile, the t-calculation of electronic word of mouth showed 5.602>1.985 which means there was a significant effect of electronic word of mouth on purchase decision. The F-calculation of celebrity endorsement and electronic word of mouth showed 49.251>3.090 which means that there was a significant effect of celebrity endorsement and electronic word of mouth on purchase decision. Based on the research, it can be concluded that celebrity endorsement partially has positive effect on purchase decision; electronic word of mouth partially has effect on purchase decision; and celebrity endorsement and electronic word of mouth simultaneously have positive effect on purchase decision.